Morphophonemics as a precursor to effective english language teachin g - Kirunda, Rebecca Florence (Kampala : Makerere University, 2000)
Thesis (M.Ed.) - Makerere University, 2000.
Includes bibliographical references (p. 96-100)
Keywords: English language -- Study and teaching (secondary) -- Uganda